The Californians - Fisher, Walter M. (Walter Mulrea), 1849-1919. (London : Macmillan and Co., 1876)
English writer Walter Mulrea Fisher (1849-1919) lived in California for four years in the 1870s. The Californians (1876) is his account of that stay, a gossipy social analysis of the people of California, with only a brief summary of California geography and climate and no itinerary of his travels. Thus there are separate chapters for early California settlers, Hispanic Californians, women and family life, Chinese immigrants, politicians, local authors and newspaper publishing, and religious life.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
digitized
digitized
Description based on print version record.
Keywords: Ethnic groups -- California; Women -- California; Urbanization -- California; Real estate development -- California; Law -- Political aspects -- California; Religion and ethics -- California; Business -- California; California -- Description and travel; California -- Social life and customs